FAECAL OCCULT BLOOD TEST IN INTESTINAL HELMINTHIASIS - ARUNAVA KALI; S. SRIRANGARAJ; K.S. SEETHA (International Journal of Pharma and Bio Sciences, 2014)
Enteric helminthic infection is one of the most important public health issues in developing countries. These infections are transmitted by faeco-oral route and cause significant morbidity among patients of all age groups, especially in school age and pre-school age children. The clinical presentation may be vague and non-specific. Frequently, patients with enteric helminthic infection (especially in case of hookworm) have occult lower intestinal bleeding which may be a useful adjunct to parasitic diagnosis. In this study, faecal samples from 716 patients were screened for occult blood and enteric parasites. Out of 716 patients, 6% and 5.16% were positive for faecal occult blood test (FOBT) and enteric helminthes respectively. The sensitivity and specificity of FOBT were 59.50% and 96.90%. The results indicate the need to consider parasitic load and retesting of successive stool samples while interpreting FOBT.